(untitled) (Jurnal Pendidikan Fisika, 2023)
This research departs from the problem of limited tools and practicum materials in the laboratory, and students need help understanding the concept of momentum and impulse material. An effort to overcome these problems is to develop an electronic student worksheet using a problem-based learning model with the Wizer.me platform. This study aims to describe the development process, validity level, and practicality of electronic student worksheets using the problem-based learning model with the Wizer.me platform on momentum and impulse material. The research method used is research and development (R&D) with the ADDIE development model. The population of this research is all class X MIPA SMA Negeri 13 Garut, consisting of seven classes with 252 students. The research sample was taken by using the cluster random sampling technique for classes X MIPA 1 and X MIPA 2, with 36 students in each class. The data analysis technique used in processing the validation results was Aiken’s V index. The results showed that the Aiken index of material, media, and learning experts were respectively 0.91, 0.94, and 0.96 with excellent categories, and the average practicality percentage is 89% with efficient criteria. Therefore, it can be concluded that the electronic student worksheets developed using a problem-based learning model with the Wizer.me platform on the momentum and impulse material meets valid and practical criteria for use in the learning process.